OBLICZ:
F = x - (2x + 5) = x - 2x - 5 = -x - 5
G = 6 - (-3x + 2) = 6 + 3x - 2 = 3x + 4
H = 5 - (2x + 4) = 5 - 2x - 4 = -2x + 1
SPRAWDŹ:
A. F + G = H
(-x - 5) + (3x + 4) = -x - 5 + 3x + 4 = 2x - 1
FAŁSZ
B. F + H = G
(-x - 5) + (-2x + 1) = -x - 5 - 2x + 1 = -3x - 4
FAŁSZ
C. G + H = F
(3x + 4) + (-2x + 1) = 3x + 4 - 2x + 1 = x + 5
FAŁSZ
D. F + G + H
(-x - 5) + (-2x + 1) + (3x + 4) = -x - 5 - 2x + 1 + 3x +4 = -3x + 3x - 5 + 5 = 0
PRAWDA
czyli:
A. fałsz
B. fałsz
C. fałsz
D. prawda
Mam nadzieję, że pomogłam. Pozdrawiam!